Old drugs for new uses: pharmacokinetic assessment to support oxfendazole repurposing as a flukicidal compound - Chiappetta, Valentina (2025)
Fasciolosis is a parasitic disease caused by liverflukes Fasciola hepatica that affects domestic ruminants and humans. The disease leads to significant economic losses in animal production due to decreased productivity. Human fasciolosis is considered a neglected tropical disease by the World Health Organization. Chemotherapy remains the most effective strategy for controlling fasciolosis in animals: However, its indiscriminate use resulted in the development of resistance to most effective flukicidal drugs. Oxfendazole (OFZ) is an old and well-established nematodicidal drug, with very limited activity against the trematode F. hepatica. In anattempt to repurpose its use, promissory flukicidal efficacies have been observed when OFZ was used at higher dose rates both in sheepand pigs.